ADMINISTRASI NEGARA KONTEMPORER UNTUK INOVASI PELAYANAN PUBLIK - Rosyadi, Slamet (JI@P, 2017)
The environment public administration provides the situation is unpredictable and uncertain. Therefore, public administration needs to be supported by adequate capability in order to organize public services that are more innovative. The scarcity of budget and demands of an increasingly diverse public administration encourages countries to do public service innovation. To facilitate the innovation of public service required three capabilities: thinking ahead, thinking again and thinking across. The third of these capabilities need to be supported with organizational climate that supports innovation process, namely the availability of resources, the new leadership styles, spaces learning and incentives. Key Words: Public administration, inovation, capability, public service